2021
DOI: 10.14797/rkqn5397
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pulmonary Hypertension in Left Heart Disease

Abstract: Pulmonary hypertension due to left heart diseases (PH-LHD) is the most prevalent form of pulmonary hypertension. It frequently complicates heart failure with reduced ejection fraction (HFrEF) or preserved ejection fraction (HFpEF) and negatively impacts prognosis, particularly when a precapillary component is present. PH-LHD is distinctive from pulmonary arterial hypertension (PAH) even though both conditions may share some common characteristics. In addition, the mechanisms involved in the development of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Multivariate analysis showed that the risk ratio for mortality from any cause or rehospitalization and cardiovascular mortality for patients with a high probability of pulmonary hypertension was 1.67 and 2.7 times higher, respectively, than for patients with a low or moderate probability of PH, but decreased ejection fraction. Left ventricular fraction (LVEF<40) and proper ventricular function (reduced RVF) were not related to the primary outcome of the patient (9). These results are in line with the present study's findings.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Multivariate analysis showed that the risk ratio for mortality from any cause or rehospitalization and cardiovascular mortality for patients with a high probability of pulmonary hypertension was 1.67 and 2.7 times higher, respectively, than for patients with a low or moderate probability of PH, but decreased ejection fraction. Left ventricular fraction (LVEF<40) and proper ventricular function (reduced RVF) were not related to the primary outcome of the patient (9). These results are in line with the present study's findings.…”
Section: Discussionsupporting
confidence: 92%
“…In other studies, it has been reported that the predictive value of LVEF is not linear and is influenced by various intervening factors (25). Patients without RV dysfunction without PH were not at increased risk of mortality during one year of follow-up (9). These results show that the presence of PH with RV dysfunction provides important prognostic information for ADHF patients, which can help manage and evaluate ADHF patients.The results of a retrospective study by Dziewięcka et al on 502 patients with dilated cardiomyopathy (DCM) also showed that patients with a high and moderate probability of pulmonary hypertension (TRV > 3.4 m/s and TRV 2.9-3.4 m/s) on echocardiography were at increased risk.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Pulmonary hypertension frequently accompanies left heart disease (PHLHD) and is associated with worse prognosis than left heart disease without pulmonary hypertension [1][2][3]. Because of its frequency, prognostic implications, diagnostic challenges, and evolving treatment strategies, PHLHD is a frequent subject of publications [4 && , [5][6][7][8][9][10][11][12][13][14]. Diagnosis of PHLHD (group 2) requires recognition of patient characteristics that pose risk for having left heart disease.…”
Section: Introductionmentioning
confidence: 99%